Unraveling the Complexity of Amyotrophic Lateral Sclerosis Survival Prediction - Pfohl, Stephen R.; Kim, Renaid B.; Coan, Grant S.; Mitchell, Cassie S. (Frontiers in Neuroinformatics, 2018)
Objective: The heterogeneity of Amyotrophic Lateral Sclerosis (ALS) survival duration, which varies from <1-year to >10-years, challenges clinical decisions and trials. Utilizing data from 801 deceased ALS patients, we: 1) assess the underlying complex relationships among common clinical ALS metrics; 2) identify which clinical ALS metrics are the “best” survival predictors and how their predictive ability changes as a function of disease progression. Methods: Analyses included examination of relationships within the raw data as well as the construction of interactive survival regression and classification models (general linear model and random forests model). Dimensionality reduction and feature clustering enabled decomposition of clinical variable contributions. Thirty-eight metrics were utilized, including Medical Research Council (MRC) muscle scores; respiratory function, including forced vital capacity (FVC) and FVC % predicted, oxygen saturation, negative inspiratory flow (NIF); the Revised ALS Functional Rating Scale (ALSFRS-R) and its activities of daily living (ADL) and respiratory sub-scores; body weight; onset type, onset age, gender, and height. Prognostic random forest models confirm the dominance of patient age-related parameters decline in classifying survival at thresholds of 30, 60, 90, 180-days and 1, 2, 3, 4, and 5-years. Results: Collective prognostic insight derived from the overall investigation includes: multi-dimensionality of ALSFRS-R scores suggests cautious usage for survival forecasting; upper and lower extremities independently degenerate and are autonomous from respiratory decline, with the latter associating with nearer-to-death classifications; height and weight-based metrics are auxiliary predictors for farther-from-death classifications; sex and onset site (limb, bulbar) are not independent survival predictors due to age co-correlation. Conclusions: The dimensionality and fluctuating predictors of ALS survival must be considered when developing predictive models for clinical trial development or in-clinic usage. Additional independent metrics and possible revisions to current metrics, like the ALSFRS-R, are needed to capture the underlying complexity needed for population and personalized forecasting of survival.